Character Education Analysis Represented in English Textbooks for Secondary School Based on the 2013 Curriculum in Indonesia - Reko Serasi; Liya Peransiska; M. Arif Rahman Hakim (Metathesis: Journal of English Language, Literature, and Teaching, 2022)
This research is focused on content analysis of character education potrayed in English texbooks based on the Indonesia 2013 curriculum to find out the types of character education values in English textbooks and how educational character values were included into English textbooks for secondary schools. In fact, moral degradation among the youth in the modern era is becoming trends. Therefore, in this study, researchers want to focus on content analysis of character education potrayed in English texbooks based on the Indonesia 2013 curriculum based on 18 character values issued by Indonesian government. In this study, the researchers used a content analysis technique under the formula of qualitative research method. The result of the study showed that the total frequency of character value based on first semester that emerged in the textbook 1 gained 73 times or percentage (39%). The value of related to self was the most frequent value with 40 times. Then, it was followed by related to others with 17 times. The values have small proportion are related to nation and additional values; the character not existed in English textbook 1 represented first semester is related to God. The total frequency of character value based on first semester that emerged in the textbook 2 was 115 times or percentage (61%), the value of related to self was the most frequent value with 72 times. The values have small proportion are related to others, related to environment, related to nation, related to good and additional values. These findings lead to the conclusion that the upcoming textbooks should pay attention on the character values official 2013 curriculum for students in secondary school contain a lot of character education